Comparing health risk behaviors of Franklin County youth with their national and statewide counterparts: An ecological study in the state of Kentucky - Walston, Herman; Meshack, Angela; Latham, Timothy; Peters III, Ronald; Gans, Timothy; Peters, Anthony; Majid, Warith (International Journal of Health, 2018)
While national surveillance studies have stratified high school students’ health behavior outcomes, few ecological data sets have been explored, collected, and analyzed on the unique health problems of minority children. An area for which limited data on minority youth has been collected is Franklin County, home of the state capital of Kentucky. In the current study, we use baseline data collected in 2015 from students attending two high schools that were sites for Kentucky State University’s Youth Empowerment Project. We hypothesize that youth who reside in Franklin County would report lower maladjusted behaviors than their national and statewide counterparts in the same year of observation. Data analyses confirm that compared to their national- and state-level counterparts, Franklin County high school students were less likely to report riding with a driver who had been drinking alcohol, engaging in sexual intercourse, drinking alcohol before sexual intercourse, and experiencing non-condom use when engaged in sexual intercourse, forced sexual intercourse, dating violence, cyber bullying, suicidal ideation, and drug use. These findings suggest that Franklin County high school students may be exposed to environmental variables that may be preventive to maladjusted behaviors.